The concept of time according to Gilles Deleuze-time crystals and their impact on shaping human subjectivity (Damascus University Journal of arts and humanities sciences, 2026)
This paper explores the intriguing concept of time as articulated by the French philosopher Gilles Deleuze. Deleuze views time not as a linear progression but rather as a rich synthesis that can be examined and understood through three distinct frameworks: the synthesis of habit, the synthesis of memory, and the synthesis of eternal return. Together, these perspectives shape our understanding of time and are vividly illustrated through what Deleuze refers to as “time crystals” employed by Deleuze in his examination of cinema. In this context, time assumes the role of movement and is likened to a form ofcurrency within the film industry, signifying that a film comes to an end when financial support is withdrawn. Consequently, time emerges as the essential element facilitating the sequential arrangement of cinematic images, thereby enabling the presentation of a complete scene within the dynamic framework of time crystals. Although Deleuze specifically applied this crystalline model to cinema, it transcends this singular domain; it can also serve as a valuable framework for comprehending human subjectivity, which continuously dissolves and reconstitutes itself within the temporal experience reflected in these crystals. While Deleuze's crystalline metaphor is rooted in the study of cinema, its implications extend far beyond this medium. It serves as a powerful framework for comprehending human subjectivity, which continuously dissolves and reconstitutes itself in the context of the time reflected in these crystals. Through this lens, we gain deeper insights into how our experiences and identities are shaped by the multifaceted nature of time itself. This research seeks to delve into the intricate mechanisms by which temporal dimensions intersect to shape human subjectivity, viewing it as a dynamic entity that evolves in every moment according to the shifting pathways of time's synthesis within the crystal. This process unfolds through the manifestation of the virtual and the transformation of what is realized into a hypothesis within the smallest loop of the crystal, where time reveals itself in its most unadulterated form.
Keywords: Crystals of Time; Human Subjectivity; The Virtual; Eternal Return; Pure Past